Molecular identification ofNocardiaspecies causing endophthalmitis using multilocus sequence analysis (MLSA): a 10‐year perspective. Issue 5 (May 2020) - Gnanam, Hariharan; Rajapandian, Siva Ganesa Karthikeyan; Gunasekaran, Rameshkumar; Prithiviraj, Swasthikka Roshni; Ravindran, Ram Sudarshan; Sen, Sagnik; Prajna, Lalitha
Abstract : Introduction. : Nocardia spp. can cause several ocular infections, such as keratitis, endophthalmitis and scleral abscesses. Molecular identification of Nocardia spp. by 16S rDNA sequencing is the gold standard method at present for species identification, but closely related species can only be identified by multilocus sequence analysis (MLSA) of housekeeping genes. Aim. : The major objective was to profile Nocardia species, antibiotic susceptibility patterns and clinical outcomes in endophthalmitis patients. Methodology. : Between January 2009 and December 2018, endophthalmitis patients who were diagnosed with Nocardia infection based on microscopic and culture characteristics were selected. Antibacterial susceptibility tests were performed and Nocardia speciation was performed using MLSA and phylogenetic tree analysis of the 16 s rRNA gene and the gyrB, hsp65 and secA1 genes. Results. : A total of 43 culture‐proven patients were identified during the study period. All isolates were 100 % sensitive to amikacin and 98 % resistant to ceftazidime. Fluoroquinolone sensitivity was observed in the range of 58 to 72 %. Year‐wise analysis of antibiotic resistance patterns revealed there was a significant increase in resistance to fluoroquinolones. Twenty‐two isolates were stored and six different species were identified. Nocardia farcinica ( n =10) was found to be the most predominant, followed by Nocardia cyriacigeorgica ( n =4), Nocardia otitidiscaviarum ( n =3), Nocardia amikacinitolerans ( n =2), Nocardia puris ( n =2) and Nocardia higoensis ( n =1). Conclusions. : N. farcinica is the major pathogen, and this is the first report to identify N. otitidiscaviarum, N. amikacinitolerans and N. higoensis as causing endophthalmitis. Overall, visual outcomes were mostly poor even after aggressive management.